1981
DOI: 10.2214/ajr.136.2.381
|View full text |Cite
|
Sign up to set email alerts
|

CT of cervical lymph node cancer

Abstract: Ten patients with carcinoma of the base of the tongue, larynx, and hypopharynx who had radical neck dissection form this group (table 2). For gross pathologic correlation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
1
9

Year Published

1982
1982
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(57 citation statements)
references
References 7 publications
0
47
1
9
Order By: Relevance
“…The CT scan can differentiate a single enlarged lymph node from a conglomerate of matted lymph nodes and it can identify central lymph node necrosis. 21 Close et al 22 found that the CT scan upstaged the clinically negative neck in 67% of cases of oral cavity and oropharyngeal carcinoma and several studies have shown a greater than 90% accuracy rate for CT scanning of pathologic neck disease. [17][18][19] In the current study, imaging had an 84% sensitivity rate in detecting pathologic lymph node disease in cN-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…The CT scan can differentiate a single enlarged lymph node from a conglomerate of matted lymph nodes and it can identify central lymph node necrosis. 21 Close et al 22 found that the CT scan upstaged the clinically negative neck in 67% of cases of oral cavity and oropharyngeal carcinoma and several studies have shown a greater than 90% accuracy rate for CT scanning of pathologic neck disease. [17][18][19] In the current study, imaging had an 84% sensitivity rate in detecting pathologic lymph node disease in cN-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Using these imaging modalities, the criteria for diagnosing metastatic nodes is mainly dimensional. Measurements include the minimum transaxial diameter, the maximum transaxial diameter or a ratio between the maximum longitudinal and the maximum axial diameters (3)(4)(5)(6)(7). Other parameters, such as morphological criteria or the pattern of enhancement, are regarded as less important in this setting.…”
mentioning
confidence: 99%
“…Second, meta· static nodes showed a more rounded configuration than A precise evaluation of the presence of meta· stasis to the cervical lymph nodes is mandatory in the management of head and neck malignancies. X-ray computed tomography (CT), 1 magnetic resonance imaging (MRI), and ultrasound 2 -4 have been used to evaluate lymphadenopathy in the neck. Recent reports on ultrasonography in the neck suggest its high efficiency in detecting small, nonpalpable lymphadenopathy.…”
mentioning
confidence: 99%